PENGARUH DIGITAL MARKETING TERHADAP MINAT BELI KOSUMEN PADA MARKETPLACE SHOPEE (Fakultas Ekonomi Universitas Wisnuwardhana, 2023)
This research is used to test the magnitude of the influence of digital marketing which is based on search engine marketing indicators, websites, e-mail marketing, and social media marketing on consumer buying interest in the Shopee marketplace. The scope of this research is the influence of digital marketing variables on consumer buying interest variables. A quantitative approach was used in this study with a total of 120 respondents based on a purposive sampling technique. In this study, primary data was obtained using a questionnaire in which the questionnaire used a measurement scale, namely the Likert scale. The technique used to process the results of the respondents is simple regression analysis. Based on the results of data analysis, it was found that the two variables, namely digital marketing variables and also consumer buying interest, have a positive and significant influence. In this study, consumer buying interest was influenced by 26.8%. This study provides an overview of the theoretical application that can be used as reference material for similar research. Managerial implications in the form of suggestions for marketplace shopee in order to improve the quality of the website and social media as a means of marketing this marketplace so that there will be more and more buying interest from customers. Keywords: Consumer buying interest, Digital Marketing, Consumer Behavior